2015
DOI: 10.1111/edt.12218
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and causes of dental trauma in children living in the county of Värmland, Sweden

Abstract: The incidence rate for dental trauma has not decreased in the past 20 years, and there is an indication that parents and teachers should be more aware of the risks of dental trauma at leisure times and at school as well as during sports and exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 31 publications
(46 reference statements)
5
21
0
Order By: Relevance
“…The majority of TDIs occurred at home and at school during a physical activity that lead to fall, as demonstrated in this study; 63.1% of dental trauma occurred due to a fall followed by a collision with an object or person. Our results were consistent with the literature that reported the most common cause of injury was a fall and the home being the commonest place [ 18 , 31 ]; however, some studies concluded that TDIs occur most common in a field/playground or outdoors [ 27 , 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…The majority of TDIs occurred at home and at school during a physical activity that lead to fall, as demonstrated in this study; 63.1% of dental trauma occurred due to a fall followed by a collision with an object or person. Our results were consistent with the literature that reported the most common cause of injury was a fall and the home being the commonest place [ 18 , 31 ]; however, some studies concluded that TDIs occur most common in a field/playground or outdoors [ 27 , 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…This study found out that TDI is more prevalent in males than in females. Similar results have been reported from studies across the world [18,19,21]. This underscores the fact that outdoor activities/ travel and sports are promoted more among males rather than females, more so in India.…”
Section: Discussionsupporting
confidence: 87%
“…6 An Australian study found an incidence rate of 20 TDI per 1000 individuals per year in children aged 6-12 years. 7 Two large Swedish studies extended over several years reported incidence rates of 19 to 29 events per 1000 individuals per year, 8 and an annual incidence rate of 28%, 9 respectively. Thus, although TDI prevalence and incidence are generally high worldwide, they may vary considerably.…”
mentioning
confidence: 99%